Crosstalk between breast cancer-derived microRNAs and brain microenvironmental cells in breast cancer brain metastasis - Khan, Munazza S.; Wong, Grace L.; Zhuang, Chuling; Najjar, Mariana K.; Lo, Hui-Wen (Frontiers in Oncology, 2024)
Breast cancer is the most frequent malignancy in women, constituting 15.2% of all new cancers diagnosed in the United States. Distant breast cancer metastasis accounts for the majority of breast cancer-related deaths; brain metastasis is the third most common site for metastatic breast cancer but is associated with worst prognosis of approximately eight months of survival. Current treatment options for breast cancer brain metastasis (BCBM) are limited and ineffective. To help identify new and effective therapies for BCBM, it is important to investigate the mechanisms by which breast cancer cells metastasize to the brain and thrive in the brain microenvironment. To this end, studies have reported that primary breast tumor cells can prime brain microenvironmental cells, including, astrocytes and microglia, to promote the formation of BCBM through the release of extracellular vesicle-microRNAs (miRNAs). Breast tumor-derived miRNAs can also promote breast cancer cell invasion through the blood-brain barrier by disrupting the integrity of the brain microvascular endothelial cells. In this review, we summarize current literature on breast cancer-derived BCBM-promoting miRNAs, cover their roles in the complex steps of BCBM particularly their interactions with microenvironmental cells within the brain metastatic niche, and finally discuss their therapeutic applications in the management of BCBM.